Shift work and cancer - considerations on rationale, mechanisms, and epidemiology - Giovanni Costa; Erhard Haus; Richard Stevens (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
This paper summarizes the rationale for, possible mechanisms of, and problems related to risk assessment of the association between shift work and cancer. The mechanisms by which circadian disruption may favor the induction and/or promotion of malignant tumors are complex and multifactorial. The multilevel endocrine changes caused by circadian disruption with melatonin suppression through light at night (LAN) lead to the oncogenic targeting of the endocrine-responsive breast in women and possibly the prostate in men. Repeated phase shifting with internal desynchronization may lead to defects in the regulation of the circadian cell cycle, thus favoring uncontrolled growth. Sleep deprivation leads to the suppression of immune surveillance that may permit the establishment and/or growth of malignant clones. The epidemiological studies published so far, although dealing with large cohorts and controlling for several personal confounders, have defined the exposure to shift and/or night work rather loosely and consequently do not allow for the proper assessment of the risk connected with circadian disruption.